Synthesis of Bioderived Cinnolines and Their Flow-Based Conversion into 1,4-Dihydrocinnoline Derivatives - Devlin, Jonathan; Clogher, Richard; Baumann, Marcus (Synlett, 2020)
Starting from phenylhydrazine and glucose, a versatile cinnoline scaffold was obtained on a multigram scale and further derivatized. A simple continuous-flow hydrogenation process permits the conversion of selected cinnolines into their 1,4-dihydrocinnoline counterparts. These products are generated in high yields and high purities with residence times of less than one minute and, along with their cinnoline precursors, are expected to serve as valuable heterocyclic building blocks for future medicinal chemistry programs.
Keywords: flow synthesis; cinnolines; dihydrocinnolines; hydrogenation